Article Commentary: The Practical Application of Clinical Prediction Rules: A Commentary Using Case Examples in Surgical Patients with Degenerative Cervical Myelopathy. (December 2015) - Tetreault, Lindsay; Le, David; C⊚té, Pierre; Fehlings, Michael
Study Design: Commentary. Objective: This commentary aims to discuss the practical applications of a clinical prediction rule (CPR) developed to predict functional status in patients undergoing surgery for the treatment of degenerative cervical myelopathy. Methods: Clinical cases from the AOSpine CSM-North America study were used to illustrate the application of a prediction rule in a surgical setting and to highlight how this CPR can be used to ultimately enhance patient care. Results: A CPR combines signs and symptoms, patient characteristics, and other predictive factors to estimate disease probability, treatment prognosis, or risk of complications. These tools can influence allocation of health care resources, inform clinical decision making, and guide the design of future research studies. In a surgical setting, CPRs can be used to (1) manage patients' expectations of outcome and, in turn, improve overall satisfaction; (2) facilitate shared decision making between patient and physician; (3) identify strategies to optimize surgical results; and (4) reduce heterogeneity of care and align surgeons' perceptions of outcome with objective evidence. Conclusions: Valid and clinically-relevant CPRs have tremendous value in a surgical setting.